(untitled) (Research, Society and Development, 2022)
Metallic biomaterials in the oral cavity exposed to extreme conditions that affect it and reduce its biofunctionality. Surface modification by plasma spray oxide deposition is one of the methods used as an alternative to improve the bioactivity of Ti alloy implants. The objective of this work was to study the physicochemical surface characteristics of Ti-6Al-4V and Ti-6Al-7Nb alloys modified by TiO2 coating via plasma spray and thermochemical treatment with NaOH. The Ti-6Al-4V and Ti-6Al-7Nb alloys obtained in a cylindrical shape, sectioned in the longitudinal direction, and sectioned with dimensions of 20 mm in diameter and 2 mm in thickness, sanded and polished. The microstructure revealed using Kroll’s solution. Then, titanium oxide (TiO2) powder deposition performed on Ti-6Al-4V and Ti-6Al-7Nb samples and submitted to thermochemical treatment with NaOH solution. The physical-chemical characterizations and elemental analysis performed using argon-induced plasma emission spectrometry (ICP), X-ray fluorescein spectrometry (XRF), scanning electron microscopy (SEM), X-ray diffraction (XRD). The results showed a rough and porous TiO2 coating morphology. TiO2 deposition resulted in an apparent mixture of stoichiometric and non-stoichiometric oxides on the substrate surface, in addition to presenting an optimization in the substrate/coating interaction with the NaOH treatment, leading to an increase in the surface area. It seen that the TiO2/Ti-6Al-4V/ and TiO2/Ti-6Al-7Nb systems present good chemical adhesion between substrate and coating, and the layer formed by the TiO2 coating associated with the treatment with NaOH presents a relevant level of porosity, being an important feature for osseointegration.